Supervised exercise-based rehabilitation for people with intermittent claudication–Study protocol for a Danish implementation process (StRiDE) - Sara Fredslund Hajdú; Helle Bøgard; Thomas Vedste Aagaard; Stine Gundtoft Roikjær; Charlotte Simonÿ; Anne Dalhoff; Kim Houlind; Alexander Luijk; Ida Ulriksen; Lotte Therkildsen Jensen; Søren T. Skou; Lars Hermann Tang (PLoS ONE, 2025)
Introduction Intermittent claudication is a peripheral artery disease caused by arteriosclerosis. People with intermittent claudication experience leg cramping during walking, with relief of symptoms during rest. Evidence shows that by participating in supervised exercise therapy and smoking cessation programs, people with intermittent claudication can reduce those symptoms and improve health-related quality of life and maximal walking distance while minimizing the need for an operation. However, implementation of such health-promoting initiatives in clinical practice in Denmark and other countries is limited. This is a protocol presenting the implementation process of supervised exercise therapy and smoking cessation in a region of Denmark. Methods and analysis The implementation process is a collaboration between the municipalities in the Region of Zealand and the Department of Vascular Surgery at University Hospital Zealand. The study uses a convergent mixed-methods prospective clinical cohort design, and the theoretical frame of this implementation process follows the framework for Adapting an existing intervention to a new context (ADAPT). The process involves stakeholder engagement, ongoing evaluation through key performance indicators and relevant outcomes that will inform the implementation process across and within each municipality. Dissemination Dissemination will happen throughout the process through continued meetings with stakeholders and dissemination of performance indicators and outcome results obtained through a database. All information about the study and material will be freely available. The project is registred on Clinicalgov (NCT06299956).